2016
DOI: 10.1111/gcb.13294
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term increase in snow depth leads to compositional changes in arctic ectomycorrhizal fungal communities

Abstract: Many arctic ecological processes are regulated by soil temperature that is tightly interconnected with snow cover distribution and persistence. Recently, various climate-induced changes have been observed in arctic tundra ecosystems, e.g. shrub expansion, resulting in reduction in albedo and greater C fixation in aboveground vegetation as well as increased rates of soil C mobilization by microbes. Importantly, the net effects of these shifts are unknown, in part because our understanding of belowground process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 119 publications
(199 reference statements)
3
31
1
Order By: Relevance
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, ; Geml et al., , ; Morgado et al., , ; Mundra et al., ; Semenova et al., , ). However, further investigations are needed, since complex interactions may occur with habitat type (Morgado et al., ), changes in N deposition (Lilleskov et al., ), date of snowmelt (Schmidt et al., ), microbial activity in winter (Aanderud, Jones, Schoolmaster, Fierer, & Lennon, ; Buckeridge & Grogan, ; Schimel, Bilbrough, & Welker, ; Semenchuk et al., ), floristic composition or climatic variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, ; Geml et al., , ; Morgado et al., , ; Mundra et al., ; Semenova et al., , ). However, further investigations are needed, since complex interactions may occur with habitat type (Morgado et al., ), changes in N deposition (Lilleskov et al., ), date of snowmelt (Schmidt et al., ), microbial activity in winter (Aanderud, Jones, Schoolmaster, Fierer, & Lennon, ; Buckeridge & Grogan, ; Schimel, Bilbrough, & Welker, ; Semenchuk et al., ), floristic composition or climatic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, 2012;Geml et al, 2015Geml et al, , 2016Morgado et al, 2015Morgado et al, , 2016Mundra et al, 2016;Semenova et al, 2015Semenova et al, , 2016.…”
Section: Potential Impacts Of Environmental Changes On Fungal Commumentioning
confidence: 99%
See 1 more Smart Citation
“…Biological drivers potentially tied to fluxes are improved species performance [ Chapin and Shaver , ; Oberbauer et al, ], shift in plant communities [ Walker et al , ; Schuur et al , ; Myers‐Smith et al , ; Hollister et al , ], and herbivory [ Welker et al , ; Kelsey et al , ]. The warming of soils and thawing of permafrost stimulate soil organic matter decomposition [ Mackelprang et al , ; Schädel et al , ; Xue et al , ] and increase heterotrophic respiration from soils result in a positive feedback to the atmospheric CO 2 concentration but will depend on snow accumulation [ Nowinski et al , ; Blanc‐Betes et al , ] and changes in soil community abundance and composition [ Mohan et al , ; Morgado et al , ; Parker et al , ; Semenova et al , ; Geml et al , ; Morgado et al , ]. Increased CO 2 loss may, however, be counteracted by increases in net primary production (NPP) as plant productivity increases [ Epstein et al , ] and the plant community shifts from graminoid to shrub dominance [ Sturm et al , ; Walker et al , ; Myers‐Smith et al , ; Pearson et al , ; Hollister et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Together these mechanisms can increase water and nutrient supply for soil microbes and plants (Groffman et al, 2006;Buckeridge et al, 2010). In addition, greater snow accumulation could also alter both plant and microbial community compositions (Zinger et al, 2009;Kreyling et al, 2012;Bokhorst et al, 2013;Morgado et al, 2016;Semenova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%